Cyprus : 2011 Article IV Consultation: Staff Report; Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report, 2011)
The 2011 Article IV Consultation report discusses the Cypriot economy, which faces strong headwinds and downside risks owing to financial turbulence in the euro area and the large exposure of Cypriot banks to Greece. Executive Directors noted that Cyprus faces daunting economic challenges in the face of faltering external demand and worsening domestic financial conditions. Directors urged the authorities to act forcefully to restore sound public finances and safeguard the stability of the banking system.